Long-acting muscarinic antagonists vs. long-acting β 2 agonists in COPD exacerbations: a systematic review and meta-analysis - Israel Silva Maia; Mariângela Pimentel Pincelli; Victor Figueiredo Leite; João Amadera; Anna Maria Buehler (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To determine whether long-acting muscarinic antagonists (LAMAs) provide superior therapeutic effects over long-acting β2 agonists (LABAs) for preventing COPD exacerbations. Methods: This was a systematic review and meta-analysis of randomized clinical trials involving patients with stable, moderate to severe COPD according to the Global Initiative for Chronic Obstructive Lung Disease criteria, treated with a LAMA (i.e., tiotropium bromide, aclidinium, or glycopyrronium), followed for at least 12 weeks and compared with controls using a LABA in isolation or in combination with a corticosteroid. Results: A total of 2,622 studies were analyzed for possible inclusion on the basis of their title and abstract; 9 studies (17,120 participants) were included in the analysis. In comparison with LABAs, LAMAs led to a greater decrease in the exacerbation rate ratio (relative risk [RR] = 0.88; 95% CI: 0.84-0.93]; a lower proportion of patients who experienced at least one exacerbation (RR = 0.90; 95% CI: 0.87-0.94; p < 0.00001); a lower risk of exacerbation-related hospitalizations (RR = 0.78; 95% CI: 0.69-0.87; p < 0.0001); and a lower number of serious adverse events (RR = 0.81; 95% CI: 0.67-0.96; p = 0.0002). The overall quality of evidence was moderate for all outcomes. Conclusions: The major findings of this systematic review and meta-analysis were that LAMAs significantly reduced the exacerbation rate (exacerbation episodes/year), as well as the number of exacerbation episodes, of hospitalizations, and of serious adverse events.